Comparison of Bioabsorbable and Metallic Interference Screws for Graft Fixation During ACL Reconstruction: A Meta-analysis of Randomized Controlled Trials. Issue 8 (18th August 2021) - Xu, Baoyun; Yin, Yuling; Zhu, Yanling; Yin, Yu; Fu, Weili
Background: Bioabsorbable interference screws and metallic interference screws are both widely used for graft fixation, but it remains unclear which screw type is superior. Purpose: To compare clinical outcomes and complications between bioabsorbable and metallic interference screws for anterior cruciate ligament reconstruction (ACLR). Study Design: Systematic review; Level of evidence, 1. Methods: The literature was searched for relevant randomized controlled trials published between 1966 and 2020. Two investigators independently assessed risk of bias in the included studies, and data were pooled to calculate mean differences (MDs) for continuous outcomes and risk ratios (RRs) for dichotomous outcomes, together with 95% CIs. Meta-analysis was performed using a random- or fixed-effects model, depending on the heterogeneity in the data. Results: Included were 14 randomized controlled trials involving 1032 patients who underwent ACLR: 528 patients with bioabsorbable screws and 504 patients with metallic screws. The 2 groups did not differ significantly in International Knee Documentation Committee score (RR, 1.04; 95% CI, 0.97 to 1.11), Lysholm score (MD, 0.59; 95% CI, –0.46 to 1.63), range of motion deficit (RR, 0.95; 95% CI, 0.67 to 1.34), positive pivot-shift test (RR, 0.87; 95% CI, 0.61 to 1.24), positive Lachman test (RR, 0.82; 95% CI, 0.48 to 1.39), or KT-1000 arthrometer value (MD, 0.01; 95% CI, –0.16 to 0.18). However, bioabsorbable screws were associated with a significantly higher risk of complications (RR, 1.70; 95% CI, 1.16 to 2.50), such as graft rupture, joint effusion, and infection. Conclusion: The results of this review showed that there was no difference between metallic and bioabsorbable screws for ACLR in terms of subjective knee function or knee laxity, but metallic interference screws had fewer complications.